Achieving change in primary care—effectiveness of strategies for improving implementation of complex interventions: systematic review of reviews. Issue 12 (23rd December 2015) - Lau, Rosa; Stevenson, Fiona; Ong, Bie Nio; Dziedzic, Krysia; Treweek, Shaun; Eldridge, Sandra; Everitt, Hazel; Kennedy, Anne; Qureshi, Nadeem; Rogers, Anne; Peacock, Richard; Murray, Elizabeth
Abstract : Objective: To identify, summarise and synthesise available literature on the effectiveness of implementation strategies for optimising implementation of complex interventions in primary care. Design: Systematic review of reviews. Data sources: MEDLINE, EMBASE, CINAHL, Cochrane Library and PsychINFO were searched, from first publication until December 2013; the bibliographies of relevant articles were screened for additional reports. Eligibility criteria for selecting studies: Eligible reviews had to (1) examine effectiveness of single or multifaceted implementation strategies, (2) measure health professional practice or process outcomes and (3) include studies from predominantly primary care in developed countries. Two reviewers independently screened titles/abstracts and full-text articles of potentially eligible reviews for inclusion. Data synthesis: Extracted data were synthesised using a narrative approach. Results: 91 reviews were included. The most commonly evaluated strategies were those targeted at the level of individual professionals, rather than those targeting organisations or context. These strategies (eg, audit and feedback, educational meetings, educational outreach, reminders) on their own demonstrated a small to modest improvement (2–9%) in professional practice or behaviour with considerable variability in the observed effects. The effects of multifaceted strategies targeted at professionals were mixed and not necessarily more effective than single strategies alone. There was relatively little review evidence on implementation strategies at the levels of organisation and wider context. Evidence on cost-effectiveness was limited and data on costs of different strategies were scarce and/or of low quality. Conclusions: There is a substantial literature on implementation strategies aimed at changing professional practices or behaviour. It remains unclear which implementation strategies are more likely to be effective than others and under what conditions. Future research should focus on identifying and assessing the effectiveness of strategies targeted at the wider context and organisational levels and examining the costs and cost-effectiveness of implementation strategies. PROSPERO registration number: CRD42014009410.